Collaboration in Truck Appointment System in Container Terminals - Karam, Ahmed; Azab, Ahmed E.; Eltawil, Amr B.; Reinau, Kristian Hegner (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
Due to the continual increase of the global containerized trade, many container terminals face the problem of high demands that their current resource capacity cannot afford. The consequences of such situation are not only the long queues of trucks at the entrance gates and storage yards but also the large turnaround times of trucks. In response, Truck Appointment Systems (TAS) were introduced to schedule truck arrivals in order to alleviate the terminal rush hours, however, the mandatory appointments developed by TASs have a negative impact on the operations as well as resources of the trucking companies. In recent literature, this issue was considered by introducing collaborative TAS in which the trucking companies as well as the container terminals collaborate to set the truck appointments. This work elaborates on the difference between traditional and collaborative TAS and demonstrates how collaborative TAS can improve the performance of the container terminal and reduce the cost of the trucking companies.